Kreativitas Guru dalam Penerapan Pembelajaran Al-Qur’an dengan Metode Jet Tempur di TPQ Ad-Dasuki - Zahrotul Millah (Social Science Academic, 2023)
The purpose of this research is to find out 1). Teacher Creativity in Al-Qur'an Learning at TPQ AD-Dasuki, 2). Al-Qur'an Learning with the Fighter Jet Method at TPQ Ad-Dasuki, 3). Factors supporting and inhibiting the Creativity of Teachers Learning the Qur'an using the fighter jet method at TPQ Ad-Dasuki. The method used is descriptive qualitative research. This research was conducted during the learning process during the even semester of the 2022/2023 school year using the fighter jet method. In this study, the research subjects were caregivers and also teachers who taught at TPQ Ad-Dasuki. In this study, the discussion is about teacher creativity and the methods used by teachers in the framework of the maximum Al-Qur'an learning process. In this study, to obtain information by interviewing teachers, observations were made at TPQ Ad-Dasuki and documentation. Based on the research results it can be concluded. Results of research 1). researchers can conclude that Al-Qur'an teachers have enough good creativity in choosing learning resources and are also quite creative in developing Al-Qur'an learning so that students do not get bored easily, 2). Al-Qur'an learning using the Jet Fighter method goes well and smoothly, 3). There are several supporting and inhibiting factors for the Creativity of Al-Qur'an Learning Teachers using the fighter jet method.